T cell immune senescence is associated with frailty and sarcopenia in lung transplant candidates - Joanna M. Schaenman, MD, PhD; Harry Pickering, PhD; Elaine F. Reed, PhD; Maura Rossetti, PhD; Benjamin Seligman, MD; S. Samuel Weigt, MD; Michael Shino, MD; David Sayah, MD, PhD; John Belperio, MD; Ashley Hu, MD; Ashley Prosper, MD; Kathleen Ruchalski, MD; et al. (JHLT Open)
Backgound: Older lung transplant recipients experience increased rates of adverse clinical outcomes, including infection compared with younger patients, potentially related to impaired cell-mediated immunity, frailty, and sarcopenia. Methods: Patients over age 55 years undergoing evaluation for lung transplantation were evaluated for sarcopenia by cross-sectional area and average attenuation of the pectoralis major muscle on chest computed tomography. Frailty was measured using the Fried Frailty Phenotype. Immune phenotyping was performed using multichannel flow cytometry of peripheral blood mononuclear cells (PBMC) in a total of 26 lung transplant candidates. Results: The median patient age was 65, primarily with restrictive lung disease (76.9%). Hospital readmission was associated with lower frequency of naïve CD4 (p = 0.004) and CD8 T cells (p = 0.026). Senescent CD4 (KLRG1+/CD28−) and CD8 T cells were also associated with readmission (p = 0.014 and p = 0.013, respectively), and senescent CD4 T cells were predictive of total hospital time (p = 0.003). TEMRA CD4 T cells were significantly associated with frailty (p = 0.015) and sarcopenia (p = 0.011). Senescent CD4 and CD8 T cells were significantly associated with sarcopenia (p = 0.009 and p = 0.006, respectively). Conclusions: These findings suggest that impaired cell-mediated immunity may underlie the associations between frailty and sarcopenia and poor clinical outcomes. A multifaceted approach to evaluation of older patients has the potential to improve risk stratification and inform management of immunosuppression.